Robust UV Plasmonic Properties of Co-Doped Ag2Te - Xin Su; Yuan Gao; Qi Wu; Haizeng Song; Shancheng Yan; Yi Shi (Crystals, 2022)
Ag2Te is a novel topological insulator system and a new candidate for plasmon resonance due to the existence of a Dirac cone in the low-energy region. Although the optical response spectrum of Ag2Te has been studied by theoretical and experimental methods, the plasmon resonance and stability of Co-doped Ag2Te remain elusive. Here, we theoretically report a new unconventional UV plasmon mode and its stability in Co-doped Ag2Te. Through density functional theory (DFT), we identify a deep UV plasmon mode within 15–40 eV, which results from the enhanced inter-band transition in this range. The deep UV plasmon is important for detection and lithography, but they have previously been difficult to obtain with traditional plasmon materials such as noble metals and graphene, while most of which only support plasmons in the visible and infrared spectra. Furthermore, we should highlight that the high-energy dielectric function is almost invariant under different doping amounts, indicating that the UV plasmon of Ag2Te is robust under Co doping. Our results predict a spectrum window of a robust deep UV plasmon mode for Ag2Te-related material systems.